Transferring irrigation management responsibility in Asia: Results of a workshop - Geijer, J.; Svendsen, M.; Vermillion, D. (Colombo (Sri Lanka), 1996)
8 ref.
Ilus.
Keywords: RIEGO; METODOS DE RIEGO; SISTEMAS DE RIEGO; ABASTECIMIENTO DE AGUA; TRANSFERENCIA DE TECNOLOGIA; EVALUACION; ASIA